Kernohan’s notch syndrome in acute subdural hematoma: significance of coronal views of computed tomography scan imaging for emergent preoperative diagnosis - Fauzi, Asra A.; Faiz, Rohadi A.; Faris, Muhammad; Wahyuhadi, Joni (International Journal of Research in Medical Sciences, 2017)
Kernohan’s notch has been well studied clinically and pathologically, although radiographic investigation has been rare. Here, we reported a case in which computed tomography scan imaging performed as an important tool for emergent preoperative diagnosis related to unusual neurological deficits appearance (Kernohan's notch syndrome) and evaluation of the treatment outcomes. Acute spontaneus subdural hematoma may rarely cause Kernohan Notch syndrome. The investigation of cerebral peduncles via emergent preoperative head computed tomography scan is useful and could provide an important contribution in preoperative diagnosis related to unusual neurological deficits appearance (Kernohan’s notch syndrome) and evaluation of the treatment and outcome in such cases.